The Sage handbook of qualitative data collection - Flick, Uwe 1956- (Los Angeles Sage Reference, 2018)
Qualitative research has now established itself beyond the original disciplines like sociology, anthropology and education in fields such as nursing, medicine, social work, psychology, information science and political sciences. As qualitative research has expanded, so have the number of different methods and approaches for data collection. The SAGE Handbook of Qualitative Data Collection provides an overview of the methodological developments available to social science researchers.
Charting the routes -- Concepts, contexts, basics -- Types of data and how to collect them -- Digital and internet data -- Triangulation and mixed methods -- Collecting data in specific populations.
Includes bibliographical references and indexes.
Keywords: Qualitative research; Social sciences -- Research -- Methodology